A retrospective observational study of poisoning and hanging cases during lockdown as a marker of emotional tide of COVID-19 pandemic in a tertiary care center in Northwestern India - Singh, Aradhana; Nawal, C. L.; Saini, H. L.; ., Khusboo; Yadav, Abhishek; Meena, P. D. (International Journal of Advances in Medicine, 2021)
Background: In January 2020, WHO declared the outbreak of a new coronavirus disease COVID-19 to be a public health emergency of international concern. Worldwide lockdown led to panic, mass unemployment, poverty and domestic violence. The present study was designed to observe the impact of lockdown on the spectrum of medico-legal cases being admitted with drastic events of poisoning and hanging. Methods:In this retrospective, observational and comparative study, around 131 patients were recruited from the admitted patients in the medicine wards in SMS medical college and hospital during COVID-19 lockdown period from 23 March 2020 to 31 May 2020 after applying inclusion and exclusion criterias. Their clinical profile were noted and comparatively assessed with patients admitted in medicine wards during adjoining pre-lockdown period, that is, from 12 January 2020 to 22 March 2020. Results: Out of 131 cases recruited during lockdown period, hanging cases were 10 (8%) while it was 10 cases out of 213 (5% )during pre-lockdown period. Organophosphorus poisoning was 4.5% and 1.4%, celphos poisoning was 3.8% and 2.3%, rat killer poisoning was 3.05% and 1.4% during lockdown and pre-lockdown period respectively. Cases due to ingestion of other than the major group of poisoning were lower (3.8%) during lockdown period while it was 10.3% during pre-lockdown period. Conclusions:Extreme negative behavioral changes precipitated by corona and this might be aggravated further by complete lockdown, to which people resorted to the means which were easily available to them at home like hanging and common poisonings.